IMPLEMENTATION OF MANAGERIAL SUPERVISION IN MADRASAH-BASED MANAGEMENT IN DISTRICT - Tb Syihabudin; Reni Suwenti (Cakrawala Pedagogik, 2022)
Madrasah-Based Management (MBM) is the autonomy given to schools to regulate all existing policies in the school environment in order to achieve school performance achievements that have been set by the Ministry of Religion. In practice, schools are given full authority to regulate learning-curriculum management, student management, infrastructure management, personnel management, financial management; public relations management, special services management and so on. The purpose of this study was to determine the implementation of supervision in the process of monitoring and evaluating MBM activities at the Pandeglang State Madrasah Aliyah. This study uses a qualitative approach. Data is generated through interviews, observation and document analysis. Based on the results of the study it was found that there were still many obstacles faced by schools in implementing MBM. So it is difficult for schools to achieve the desired performance achievements.